A Mobile Science Laboratory: Architectural Design For Secondary Schools In Uganda - Conrad M., Mubaraka; Eunice, Ndyareeba (Journal of Multidisciplinary Engineering Science and Technology (JMEST, 2019)
The teaching-learning process has remarkable effect on the entire education system in Uganda. Science subject have been peculiar in numerous forums hence a desire to change the modus operandi to demystify the illusion of difficult in students’ minds. The study was partially experimented at Hilltop S.S.S _Sheema in Western Uganda to assess the role the ICTs can make in the teaching and learning of science subjects (i.e. Biology, Chemistry and Physics). The 16 participating schools alluded to effective use of ICT when practical sessions were recorded and replayed before some students. An architectural design of a mobile science laboratory was developed which registered significant effect among students in Sheema and Uganda as a whole. The study thus recommended that schools can adopt this architecture to not only cut costs but also allow self-directed learning of the students.